A direct black-hole mass measurement in a little red dot at high redshift - Ignas Juodžbalis; Cosimo Marconcini; Francesco D’Eugenio; Roberto Maiolino; Alessandro Marconi; Hannah Übler; Jan Scholtz; Xihan Ji; Gareth C. Jones; Michele Perna; Santiago Arribas; Jake S. Bennett; et al. (Nature, 2026)
Abstract Recent discoveries of faint active galactic nuclei (AGN) at the redshift frontier have revealed a plethora of broad Hα emitters with optically red continua, named little red dots (LRDs) 1 , which comprise 15–30% of the high-redshift broad-line AGN population 2 . Owing to their peculiar properties 3–6 , modelling LRDs with standard AGN scenarios has proven challenging. In particular, the validity of single-epoch virial mass estimates in determining the black-hole masses of LRDs has been called into question, with some models claiming that masses might be overestimated by up to two orders of magnitude 7–10 . Here we report a direct, dynamical black-hole mass measurement in a strongly lensed LRD at a redshift of 7.04. The combination of lensing with deep spectroscopic data reveals a rotation curve that is inconsistent with a nuclear star cluster, yet can be well explained by Keplerian rotation around a point mass of 50 million solar masses, consistent with virial black-hole mass estimates. The Keplerian rotation leaves little room for any stellar component in a host galaxy, as we conservatively infer M BH / M ⁎ > 2 (where M BH is the black-hole mass and M ⁎ is the stellar mass). Such a ‘naked’ black hole, together with its near-pristine environment 11 , indicates that this LRD is a massive black-hole seed caught in its earliest accretion phase.